"Do we have to replace the balloon pump when it fails?". Issue 1 (18th February 2020) - Bibler, Trevor M.; Crist, Jamie M.; Malek, Janet; Childress, Andrew M.
Abstract: Mrs. Duong had coronary artery disease, ischemic cardiomyopathy, and mildly altered mental status when her case was presented before an advanced heart therapy medical review board. She was accepted for left ventricular assist device placement pending additional insight into her cognitive state. Before the LVAD could be implanted, however, Mrs. Duong went into cardiogenic shock, and her heart failure team placed an intra‐aortic balloon pump in her subclavian artery. Within two weeks, Mrs. Duong became IABP dependent and deconditioned. The attending deemed her as lacking capacity to make complex medical decisions, and the medical review board officially declined her for LVAD placement. The heart failure and CICU teams feel that Mrs. Duong is not being helped by the care they are giving her. They recommend terminal weaning of the IABP and initiation of comfort care. Her family disagrees, pointing to activities like continued eating and interacting with family. At an impasse after yet another family meeting, the attending for the heart failure team asks the clinical ethics consultant, "Do we have to replace the balloon pump when it fails?"